Effects of phenylalanine feeding on flavonoid production in Boesenbergia rotunda cell suspension cultures / Charumathi Yogarajan - Charumathi , Yogarajan (2021)
Boesenbergia rotunda, a medicinal ginger, is reported to have flavonoids and cyclohexenyl chalcone derivatives (CCD) with anti-bacterial, anti-cancer, anti-oxidant and anti-dengue properties. These compounds are obtained from rhizomes which are susceptible to biotic and abiotic stress. Hence, cell suspension cultures grown in controlled conditions are advantageous as an alternative source. The accumulation of these compounds could be enhanced using precursor. In this study, phenylalanine was used as the precursor and a feeding strategy was designed to enhance CCD (panduratin A) and other flavonoids (pinocembrin, pinostrobin and cardamonin) production. B. rotunda cell suspension cultures were established in liquid Murashige and Skoog basal medium containing 1.0 mg/L 2,4-D, 0.5 mg/L BAP and 2.0% sucrose. The established cell suspension cultures were then treated with 20.0, 40.0 and 50.0 mg/L phenylalanine at day 14 and incubated for 3, 7, 14 and 21 days before harvesting. Pinocembrin, pinostrobin, panduratin A and cardamonin were quantitated using high-performance liquid chromatography (HPLC) for each treatment. It was shown that with the addition of phenylalanine, 40 mg/L phenylalanine treated cultures showed a significant increase (p<0.05) in the content of pinocembrin after 21 days of feeding compared to control. Meanwhile, there was no significant increase in pinostrobin, cardamonin and panduratin A in the cell cultures treated with different concentrations of phenylalanine at all incubation periods tested. The significant increase in one of the flavonoids investigated in this study, which is pinocembrin could be due to the phenylalanine feeding and additional effects from stress inflicted by dying cells or nutrient depletion over the long incubation culture period. Further studies need to be carried out to confirm the effect of phenylalanine as a precursor that has enhanced pinocembrin accumulation in B. rotunda suspension cultures.